2007
DOI: 10.1080/10720160601150139
|View full text |Cite
|
Sign up to set email alerts
|

The Social Construction of Female Sexuality in a Sexualized Work Environment (SWE): The Case of a Comedy Club

Abstract: This qualitative investigation seeks to identify the sociocultural determinants and psychoemotional ramifications of essentialist gender scripting on female employees in a sexualized work environment (SWE), such as a comedy club. Sexualized work environments incorporate work and sexuality and exist on a continuum according to the frequency and intensity of the sexual economic exchange that takes place within them. In this study, interviews were conducted with 13 female employees at a comedy club in Southwest M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…Third-party observers may perceive hierarchical workplace romances to unfairly benefit the lower-status partner in an exchange of personal/sexual resources with higher ups (Mainiero, 1986). Philaretou and Young (2007) second this hypothesis with the argument that there is an exchange of resources across domains – men may offer women tangible assets (e.g. money, career advancement) along with favors and compliments for sexual attention.…”
Section: Thematic Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Third-party observers may perceive hierarchical workplace romances to unfairly benefit the lower-status partner in an exchange of personal/sexual resources with higher ups (Mainiero, 1986). Philaretou and Young (2007) second this hypothesis with the argument that there is an exchange of resources across domains – men may offer women tangible assets (e.g. money, career advancement) along with favors and compliments for sexual attention.…”
Section: Thematic Literature Reviewmentioning
confidence: 99%
“…In exchange, men may offer women tangible assets (e.g. money, advancement) along with favors and compliments (Philaretou and Young, 2007).…”
Section: Thematic Literature Reviewmentioning
confidence: 99%
“…As mentioned previously (see section 1.3.2), there are three primary factors posited for the high incidence of sexual harassment in bars: the gender roles expected of hospitality employees, the pressure to provide good customer service, and the nature of power relations between servers, customers, and managers. Hospitality work is said to be a site where traditional gender roles are played out (Folgerø & Fjeldstad, 1995;Philaretou & Young, 2007;Brunner & Dever, 2014); thus, the first reason for the prevalence of sexual harassment in bars is the perpetuation of traditional gender roles. In this industry, according to Brunner and Dever, "A defining part of these jobs is providing men with a performance of female heterosexuality" (p. 465).…”
Section: Gender Normsmentioning
confidence: 99%
“…In this industry, according to Brunner and Dever, "A defining part of these jobs is providing men with a performance of female heterosexuality" (p. 465). Philaretou and Young's (2007) study of female servers found that "[m]ale patrons tended to yield to the traditional view of women as sexual objects" in a sexualized work environment such as a bar (p. 56).…”
Section: Gender Normsmentioning
confidence: 99%
See 1 more Smart Citation